Quality Characteristics of Rice Bran Oil and the Utilization of Rice Bran from Selected Malaysian Rice Varieties - Zainuddin, Zaleenah (1990)
This study evaluated the quality of crude rice bran oil and rice bran from ten Malaysian rice varieties and commercial refined rice bran oil from Japan and India. The utilization of rice bran in bread was also studied. The rice bran was steamed(S), autoclaved(A) or left untreated(U) before oil extraction to investigate the effect of bran stabilization on oil quality. Stored rice bran (U) deteriorated rapidly and attained 10% FFA 34 hours after milling. The oil yield from bran was 8.1- 15.4%(U), 11.4-21.2%(S) and 18.4-24.4%(A). The predominant unsaturated fatty acids were oleic acid (34-43%) and linoleic acid (35-42%) in steamed bran. Unsaturated fatty acid content ranged from 73-78%(U) and 74-80%(S).